Calcified angioleiomyoma - Histopathologic and ultrasonographic analysis of the calcification process - Ming-Hsiu Hsieh; Miki Izumi; Yukio Nakatani; Kuniaki Ohara (Wolters Kluwer Medknow Publications, 2021)
Historically, angioleiomyoma is a subtype of leiomyoma that comprises about 4%-5% of all benign soft tissue tumors, and calcifications occur in 2%-3% of them. Because of the very low incidence of calcifications, their mechanism of formation is still unknown. In this article, we present the five cases of angioleiomyomas with calcification and discuss the ultrasonographic features in three of those cases. In general, from the aspect of ultrasonography, angioleiomyomas are recognized as hypoechogenic homogenous structures with peritumoral or intratumoral vascularity. However, our cases revealed heterogeneity or hyperechogenicity in inclusions, which has never been reported before. Histologically, calcifications were found not only under the dystrophic pathway which were considered in the past literature but also have the possibility under the metastatic pathway. According to our findings, we also classified the ultrasonographic patterns into three patterns according to the progression and distribution of calcifications. This is the first report to identify the location and possible pathways of calcifications and to classify the ultrasonographic features of calcified angioleiomyomas.